Content validity of the Persian version of the Pediatric Evaluation of Disability Inventory (PEDI) - Marziye Moradi Abbasabadi; Nazila Akbarfahimi; Seyed Ali Hosseini; Pouria Rezasoltani (Vesnu Publications, 2014)
Introduction: According to change in the approach to the rehabilitation of children with disability, function is an effective characteristic of the quality of life for these children. Pediatric Evaluation of Disability Inventory (PEDI) was designed to assess the function of 6 months to 7 and half years old children. The aim of this study was to translate the Pediatric Evaluation of Disability Inventory (PEDI) to Persian, and to evaluate the content validity of this Persian version. Material and methods: The translation process was based on International Quality of Life Assessment (IQOLA) Project. The Persian version of PEDI was prepared in three stages: Translation (from English to Persian and in reverse, by four translators), examination of the quality of the Persian translation (By eight rehabilitation specialists, skilled in English language), and examination of its content validity (by 15 pediatric rehabilitation specialists). Results: Respondents rated the translated version of the PEDI as acceptable. Content validity of the Persian translation of PEDI, without changing its content was confirmed. Conclusion: The results show that the Persian translation of the PEDI is acceptable and has content validity. Keywords: Functional Performance, Pediatric Evaluation of Disability Inventory (PEDI), Content Validity, Outcome Measure